Ստեփանոս Օրբէլեանի եւ Խաչատուր Կեչառեցու քաղաքական մտածողութիւնը - Վարդանեան, Արեգ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Цель данной публикации показать, что церковные деятели XIII века Степанос Орбелян и Хачатур Кечареци стремились к восстановлению Армянского царства на территории Великой Армении. В связи с этим стремлением, оба автора в своих произведениях дают конкретные оценки Армении исторической и им современной. Нужно также отметить, что Орбелян и Кечареци стремились к церковной автономии на территории Сюникской епархии. В статье приводится также критический анализ взглядов акад. Ашота Иоаннисян на политическую мысль Степаноса Орбеляна. The aim of this article is to show that late 13th century churchmen Stepanos Orbelian and Khachatur of Kecharis strived for the restoration of the Armenian kingdom in the territory of Greater Armenia. In connection with this aspiration, both authors in their works give specific assessments of historical and contemporary Armenia. It should also be noted that Stepanos Orbelian and Khachatur of Kecharis strived for ecclesiastical autonomy in the territory of Syunik Diocese. The article also critically analyzes the views of Ashot Hovhannissyan on the political thought of Stepanos Orbelian.
Keywords: Հաղորդումներ; Քաղաքականութիւն